Solusi Pengolahan Sampah dalam Problem Pencemaran Bumi untuk Kebersihan Lingkungan Hidup: Studi Syarah Hadis - Muhammad Daffa (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the hadith about cleanliness associated with waste management. This research method applies a qualitative type through library research and field studies using content analysis. The discussion of this research includes general views of cleanliness, hadith about cleanliness, and creating environmental cleanliness through waste management. This study concludes that cleanliness is the main thing in Islam as a half faith that can be done through waste management in order to create the expected environment. Waste management can be done by reducing, reusing, and recycling. The solution to overcome plastic waste is carried out through education, action, and campaigns.